1986
DOI: 10.1002/jmv.1890200106
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Antigen (AN6520), Possibly Related to Non‐A, Non‐B Hepatitis, by Monoclonal Antibodies. I

Abstract: The antibody to AN6520 antigen, which was isolated from the liver of a patient with non-A, non-B hepatitis (NANBH), has been detected frequently in convalescent sera from patients with NANBH by the passive hemagglutination (PHA) test. In a further study, we established hybridoma cells secreting antibodies against AN6520 antigen and obtained ascitic fluids with PHA titers ranging from 1:10(5) to 1:10(7). In immunodiffusion with AN6520 antigen, all monoclonal antibodies were found to form an identical precipitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Importantly for cancer biomarkers, Coller et al (2001) suggested that immunohistochemical detection of EPHX1 may be a useful diagnostic tool for hepatocellular carcinoma. Localization of EPHX1 in the membrane changes during liver pathogenesis, e.g., neoplasia (Gill et al 1983) or hepatitis infection (Akatsuka et al 1986) and is often accompanied by aberrations of EPHX1 structure (Akatsuka et al 2007). EPHX1 specifically binds hepatitis B spliced protein (HBSP) and enhances the carcinogenic effect of benzo[a]pyrene in vitro (Chen et al 2010 and 2014).…”
Section: Ephx1 Role In Human Diseasementioning
confidence: 99%
“…Importantly for cancer biomarkers, Coller et al (2001) suggested that immunohistochemical detection of EPHX1 may be a useful diagnostic tool for hepatocellular carcinoma. Localization of EPHX1 in the membrane changes during liver pathogenesis, e.g., neoplasia (Gill et al 1983) or hepatitis infection (Akatsuka et al 1986) and is often accompanied by aberrations of EPHX1 structure (Akatsuka et al 2007). EPHX1 specifically binds hepatitis B spliced protein (HBSP) and enhances the carcinogenic effect of benzo[a]pyrene in vitro (Chen et al 2010 and 2014).…”
Section: Ephx1 Role In Human Diseasementioning
confidence: 99%
“…The appearance of mEH in the blood is also associated with other types of liver disease (Hammock et al , 1984). In hepatitis C infection, we have shown that the hepatitis C-associated antigen (AN antigen) appears in the early phase of the viral infection (Akatsuka et al , 1986b), which is followed by the development of the antibody in the acute phase of hepatitis (Akatsuka et al , 1986a). In a recent study, we have shown that the AN antigen is mainly composed of mEH (Akatsuka et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit anti-AN antibody and mouse anti-AN mAb 1F12 have been described [6,7]. Rabbit anti-mEH antibody was raised by injecting a rabbit (s.c.) with 400 μg of solubilized and purified mEH three times (first with Freund's complete adjuvant, second and third immunizations with incomplete adjuvant).…”
Section: Antibodiesmentioning
confidence: 99%
“…The antibody was detected in 37.5% in NANBH cases, but not in control groups [6]. Then we developed monoclonal antibodies (mAbs) and used one of them, 1F12, to develop radioimmunoassays (RIAs) for the antigen and for the patient's antibody [7]. The antigen and antibody were detected in the acute phase and convalescent phase sera, respectively, of some patients with NANBH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation